证明: 考虑部分和
\begin{align*}
\sum_{k=1}^{n}(-1)^{k}\frac{\ln k}{k}&=2\sum_{k=1}^{[\frac{n}{2}]}\frac{\ln 2k}{2k}-\sum_{k=1}^{n}\frac{\ln k}{k}\\&=\ln 2\sum_{k=1}^{[\frac{n}{2}]}\frac{1}{k}-\sum_{[\frac{n}{2}]+1}^{n}\frac{\ln k}{k}\end{align*}设 $f(x)=\frac{\ln x}{x}$, 可知当$x >e$时为单调递减且趋于$0$函数,有估计$$\sum_{[\frac{n}{2}]+1}^{n}\int_{k}^{k+1}f(x)dx \leq \sum_{[\frac{n}{2}]+1}^{n}f(k)\leq \sum_{[\frac{n}{2}]+1}^{n}\int_{k-1}^{k}f(x)dx$$计算得$$\sum_{[\frac{n}{2}]+1}^{n}f(k)-\frac{\ln 2}{2}\ln(\frac{n^2}{2})=o(1)$$所以原式$$\sum_{k=1}^{\infty}\frac{(-1)^{k}\ln k}{k}=\ln 2 \lim_{n\to \infty}\left(\sum_{k=1}^{[n/2]}\frac{1}{k}-\ln(n/2)-\frac{\ln 2}{2}\right)=\ln 2 (\gamma-\frac{1}{2}\ln 2)$$